Numerical Integration of Bivariate Functions over a Non Rectangular Area by Using Fluctuationlessness Theorem - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2009)
Fluctuation free Matrix representation approximation Method developed by M. Demiralp call be used in approximating the multiple remainder terms of the integral of the Multivariate Taylor expansion. This provides us with it new numerical integration method for multivariate functions. However :n this paper instead of dealing with a sin-le formula which takes care of the Multiple remainder terms, it new approach is undertaken At every step of a multivariate integration only one variable is taken care of. Thus an iterative procedure which speeds up the computation rate is obtained.
Keywords: Multivariate Functions; Fluctuationlessness Theorem; Numerical Integration; Explicit Remainder Term; Taylor Expansion